Bucco-dental health state in the aged - Beatriz García Alpízar; Arturo Guerra Alfonso; Mikhail Benet Rodríguez (Medisur)
Background: The knowledge about mouth health and its risk factors acquires an important significance in the aged population. Objective: to describe the mouth health state and to evaluate the knowledge level that the studied population have about this theme. Methods: A descriptive-correlative study was done that engulfed 174 patients, of the policlinics 1, 2 and 3 from the area III of Cienfuegos municipality, Cuba. An enquiry was applied about risk factors of mouth cancer and the mouth health state of all the enquired was examined. Results: more than 50% of them stated that alcoholic beverage consumption and/or the ingestion of spiced and hot food don’t damage the mouth, or declared not having any knowledge in this field. Only the 32,2 % of the sample had teeth; and of them, 3,4 % had 20 or more teeth. More than 40 % had periodontal illness and a 44,3 % presented consumed and disarranged prosthesis. Most of them (77,1 %) needed prosthesis. The majority of lesions founded was due to wrong adapted prosthesis, which, along with smoking habits, were risk factors related to pre-malignant and malignant lesions.